SOLVING A SPECIFIC PROBLEM WHEN COMMISSIONING AN AUTOMATIC PRESSURE CONTROL SYSTEM USING SIEMENS SINAMICS V20 FREQUENCY CONVERTER: SOLVING A SPECIFIC PROBLEM WHEN COMMISSIONING AN AUTOMATIC PRESSURE CONTROL SYSTEM USING SIEMENS SINAMICS V20 FREQUENCY CONVERTER - Trifonov, Tihomir; Hadzhiivanov, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article discusses possible problems during the commissioning of a system for automatic water pressure regulation. The pressure is maintained automatically by changing the speed of rotation of the pump motor. The pump motor, in turn, is controlled by a Siemens Synamics V20 frequency converter. Thanks to a careful analysis of the parameters of the frequency converter and the system as a whole, stable operation without fluctuations has been achieved.